Outcome of Alcohol Septal Ablation in Mildly Symptomatic Patients With Hypertrophic Obstructive Cardiomyopathy: A Long‐Term Follow‐Up Study Based on the Euro‐Alcohol Septal Ablation Registry. Issue 5 (May 2017) - Veselka, Josef; Faber, Lothar; Liebregts, Max; Cooper, Robert; Januska, Jaroslav; Krejci, Jan; Bartel, Thomas; Dabrowski, Maciej; Hansen, Peter Riis; Almaas, Vibeke Marie; Seggewiss, Hubert; Horstkotte, Dieter; et al.
Abstract : Background: The long‐term efficacy and safety of alcohol septal ablation (ASA) in patients with highly symptomatic hypertrophic obstructive cardiomyopathy has been demonstrated. The aim of this study was to evaluate the long‐term outcomes of mildly symptomatic patients with hypertrophic obstructive cardiomyopathy treated with ASA. Methods and Results: We retrospectively evaluated consecutive patients enrolled in the Euro‐ASA registry (1427 patients) and identified 161 patients (53±13 years; 27% women) who were mildly symptomatic (New York Heart Association [NYHA] class II) pre‐ASA. The median (interquartile range) follow‐up was 4.8 (1.7–8.5) years. The clinical outcome was assessed and compared with the age‐ and sex‐matched general population. The 30‐day mortality after ASA was 0.6% and the annual all‐cause mortality rate was 1.7%, which was similar to the age‐ and sex‐matched general population ( P =0.62). A total of 141 (88%) patients had resting left ventricular outflow tract gradient at the last clinical checkup ≤30 mm Hg. Obstruction was reduced from 63±32 to 15±19 mm Hg ( P <0.01), and the mean NYHA class decreased from 2.0±0 to 1.3±0.1 ( P <0.01); 69%, 29%, and 2% of patients were in NYHA class I, II, and III at the last clinical checkup, respectively. Conclusions: Mildly symptomatic hypertrophic obstructive cardiomyopathy patients treated with ASA had sustained symptomatic and hemodynamic relief with a low risk of developing severe heart failure. Their survival is comparable to the general population.